2016
DOI: 10.1016/j.jvs.2015.12.046
|View full text |Cite|
|
Sign up to set email alerts
|

Transient postoperative atrial fibrillation after abdominal aortic aneurysm repair increases mortality risk

Abstract: Objective The purpose of this study was to determine whether new-onset transient postoperative atrial fibrillation (TPAF) affects mortality rates after abdominal aortic aneurysm (AAA) repair and to identify predictors for the development of TPAF. Methods Patients who underwent open aortic repair or endovascular aortic repair for a principal diagnosis AAA were retrospectively identified using the Healthcare Cost and Utilization Project-State Inpatient Database (Florida) for 2007 to 2011 and monitored longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Data from 46,928 patients who underwent vascular surgery were available from 4 studies over a mean follow-up of 29.6 AE 14.2 months. 19,41,47,57 The absolute risk increase for mortality was 8.5 per 100 patient-years for patients with perioperative AF (23.8 vs 15.3 per 100 patient-years; RR: 1.7, 95% CI: 1.2-2.4, I2 ¼ 93%).…”
Section: All-cause Deathmentioning
confidence: 98%
See 1 more Smart Citation
“…Data from 46,928 patients who underwent vascular surgery were available from 4 studies over a mean follow-up of 29.6 AE 14.2 months. 19,41,47,57 The absolute risk increase for mortality was 8.5 per 100 patient-years for patients with perioperative AF (23.8 vs 15.3 per 100 patient-years; RR: 1.7, 95% CI: 1.2-2.4, I2 ¼ 93%).…”
Section: All-cause Deathmentioning
confidence: 98%
“…2). 19,34,41,45,47,48,50,53,56,58 Data on 253,218 patients who underwent oesophageal surgery were available from 7 studies with a mean follow-up of 38.4 AE 1.9 months (Supplemental Fig. S3).…”
Section: All-cause Deathmentioning
confidence: 99%
“…Furthermore, a study on the effects of TPAF on AAA has recently been reported. 9 Thus, patients with a diagnosis of abdominal aortic dissection or aneurysm of the aorta or its branches were excluded to include only patients with occlusive disease as an indication for surgery. Also excluded were those with a pre-existing diagnosis of AF to ensure that all cases were new onset.…”
Section: Methodsmentioning
confidence: 99%
“…1 It was then further classified as TPAF or no-TPAF using the same method the authors have used in previous studies. [8][9][10] Two criteria were used to identify patients who developed TPAF. First, the patient should not have had a prior known history of AF (no AF in the 1 year before surgery and no AF present on admission).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation